Features of the influence of the performance of eurhythmic exercises on the mental state of a person (the results of the experimental research) - Borodulkina , Tetiana (Psychological Prospects Journal, 2023)
Purpose. Based on the analysis of the results of three experimental studies of the effectiveness of the eurythmic exercises, describe the features of their impact on the mental state of a person.Methods. Experiment; self-assessment of mental states; a modified version of the methodology for assessing mental activation, interest, emotional tone, tension and comfort (according to L. Kurganskyi and T. Nemchyn); frequency analysis; t-Student test for paired samples; t-Student's test for independent samples, focus groups.Results. The results of numerous foreign studies on the effectiveness of therapeutic eurythmy confirm its positive health-improving effect for patients with some chronic diseases and for healthy people. Foreign scientists have proven that in most cases, therapeutic eurythmy helps to reduce stress and fatigue, increase the quality of life and general well-being of a person. The results obtained by the author of the article in all three conducted experimental studies testify to the positive dynamics of the mental states of the participants of the experimental groups; no cases of deterioration of the mental state after performing eurythmic exercises were found. The results of Experiment 2 were fully reproduced in Experiment 3 (increase in indicators of attentiveness, concentration, calmness, indifference, carelessness, relaxation, reasoning, participants felt more rested). The effect of performing eurythmic exercises in Experiment 3 was more significant - out of 20 scales proposed for self-assessment, positive changes were found in 15 scales after performing eurythmic exercises.Conclusions. Performing eurythmic exercises in all three experimental studies contributed to the improvement of the mental state of the participants according to many important characteristics; no deterioration of the mental state was detected at all. The obtained results give us the opportunity to consider the conducted experiments successful. Our assumption that performing eurythmic exercises can help improve and stabilize a person's mental state has been confirmed. We consider the continuation of a series of experiments to test the effectiveness of various stabilizing exercises, in particular, eurythmic ones, as prospects for further research.
Keywords: stabilization of the mental state; stabilization exercises; experiment; techniques for overcoming stress; therapeutic eurythmy; crisis assistance; war trauma